Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kreatif dan Hasil Belajar Siswa dalam Menyusun Laporan Percobaan pada Siswa Kelas IX B SMP Negeri 7 Rantau Bayur - Isnayati, Isnayati; Aryani, Dwi; Fransiska, Fika; Rohmadhawati, Desi Agustina; Effendi, Darwin; Rukiyah, Siti (Universitas Islam Sumatera Utara, 2025)
This classroom action research (CAR) investigates the effectiveness of the discovery learning model in enhancing students’ creative thinking abilities and learning outcomes, particularly in preparing experimental reports. The discovery learning model engages students in identifying concepts independently through observation and experimentation, fostering active participation and deeper understanding. The study was conducted in two cycles involving 31 ninth-grade students from Class IX B at SMP Negeri 7 Rantau Bayur, Banyuasin Regency. Data collection utilized both test and non-test techniques. The results showed significant improvements across both cycles. In Cycle I, 61% of students (19 individuals) demonstrated the ability to analyze, which increased to 96% (30 individuals) in Cycle II. Similarly, students’ ability to prepare experimental reports rose from 51% (16 students) in Cycle I to 87% (27 students) in Cycle II. These findings indicate that the implementation of the discovery learning model effectively supports the development of students’ analytical and writing skills. The learning objectives were successfully achieved by Cycle II, rendering further cycles unnecessary. This study supports the use of discovery-based instruction in improving critical competencies in science learning.